Recruitment strategies for the genetics of Alzheimer disease in the Puerto Rican population: Epidemiology / Innovative methods in epidemiology (i.e., assessment methods, design, recruitment strategies, statistical methods, etc.). (7th December 2020) - Silva, Concepcion; Mena, Pedro Ramon; Tejada, Sergio; Adams, Larry D; Rodriguez, Vanessa C; Celis, Katrina; Prough, Michael; Bussies, Parker; Sierra‐Lopez, Carolina B; Contreras, Maricarmen; Manrique, Patricia; Feliciano, Nereida I; et al.
Abstract: Background: With over 5.1 million individuals, the Puerto Rican population makes up over 1.5% of the US population and is the 2nd largest Hispanic/Latino population in the continental US. There are an estimated of 60, 000 cases of AD on the island. The Puerto Rico Alzheimer's and Related Dementias Initiatives (PRADI) cohort will both leverage and complement existing AD Resources, the Alzheimer Disease Sequencing Project (ADSP) with the inclusion of a diverse and underrepresented population. At present, the cohort consists of a total of 935 total participants including individuals from 115 multiplex AD families. There are 418 cases of dementia, 217 mild cognitive impairment, and 300 unrelated and family‐based controls. Method: We examined the most successful strategy to recruit cases and controls as well as multiplex families for both case/control and family‐based genetic studies. We began by engaging a wide range of stakeholders across the island. The core activities of our team include relationship building, partnership development and maintenance, and coalition building. For the community outreach, we utilize mass media like newspapers, radio interviews, and focal group presentations and engaged the following stakeholder groups: Alzheimer disease day care centers, elderly housing in San Juan, senior day care centers, non‐profit organizations, private neurology offices, and other community‐based organizations such as the Alzheimer's Association. Result: The percent of patients recruited through each stakeholder group were 45.76% (428/935) from community outreach, 34.33% (321/935) from private neurologist practices, 18.93% (177/935) from senior day care centers and 0.96% (9/935) from Alzheimer disease day care centers. The mean age and standard deviation of cases and controls were 78.22 years (±9.37) and 70.84 years (±7.92) respectively. Examining the data with respect to multiplex family structure, we found that 53.77% of the families (including the largest families) came from private physician referral. Conclusion: Partnering with diverse stakeholders and building coalitions proved to be effective as an outreach method for recruitment. Private physicians remain an excellent source for the identification of multiplex AD families for family‐based genetics study. Outreach community‐based approaches are highly successful mechanisms to educate and engage participants in genetic research.